Hubungan Antara Sikap Penggunaan Smartphone dengan Kualitas Tidur pada Siswa SMA Kartini Batam - Ibrahim; Ade Riki Harahap; Filsi Putri Parbo (Universitas Batam, 2022)
Background: Smartphones have now become a special need for everyone, especially teenagers. Excessive smartphone use can interfere with sleep quality. Lack of individual ability to control the intensity of smartphone use can result in poor sleep quality. Teenagers need more bedtime no less than 8 hours every night. Methods: The research used an observational analyticmethod by the cross sectional approach. The data collection technique used the Probability Sampling technique using the simple random sampling method with a sample of 105 students in 2021. The data collection used two questionnaires, namely the Smartphone Addiction questionnaire for the intensity of smartphone use and the Pittsburgh Sleep Quality Index (PSQI) questionnaire for sleep quality. The data were then analyzed using Fisher's exact test. Results: There were moderate smartphone use attitudes with poor sleep quality, namely 77 people (73.3%), and high smartphone use attitudes with poor sleep quality, namely 12 people (11.4%). Based on the results of the study, none of the respondents with high smartphone use attitudes had good sleep quality (0%). Fisher's test results obtained p value = 0.028 (p <0.05). Conclusion:According to this research, it can be concluded that there was a correlation between the smartphone usage attitude with the students’ sleeping quality at Kartini Batam Senior High School.